Microfiltración apical entre tres cementos utilizados en obturación retrógrada - Legarda Canales, Vinicio Vladimir (2019)
Objective: To determine the apical microfiltration of three cements used in retrograde obturation. Methods: 45 monoradicular pieces standardized to 16 mm in length were instrumented with manual ProTaper® system and irrigated with 5.25% NaClO. The samples were sealed with ProTaper® F3 main cone and Denstply® accessories #A and #B; an apical recession of 3 mm was performed, subsequently a 3 mm of obturation was removed with ultrasound (Satelec Acteon) using tip s12/70D; the samples were divided into three groups to perform retrograde filling, each with different sealing cements. The samples were incubated at 37°C for 3 days; then covered with nail varnish except 2 mm apical to be immersed in 1% methylene blue for 48 hours, washed and longitudinally cut with #2 diamond disc for analysis in the stereo microscope (EduBlue ED 1402S), with the help of a micrometer (Stainless Hardened); different values of each group were obtained, then analyzed through comparison of means and parametric tests. Results: The average evaluation of the microfiltration produced by the retrograde filling indicates that: the MTA® presented a value of 87.33 ± 9.61 μm (14.57%), followed by the Biodentine ® with 136 ± 12.42 μm ( 22.69%), compared to the IRM® with the highest amount of microfiltration with a value of 376 ± 12.98 μm (62.74%). Conclusions: When comparing the means and percentages of the apical microfiltration of the IRM®, Biodentine® and MTA® cements; it was evident that the MTA® showed the lowest microfiltration value.